Cochrane Database of Systematic Reviews 2009
DOI: 10.1002/14651858.cd007719
|View full text |Cite
|
Sign up to set email alerts
|

Routine vitamin A supplementation for the prevention of blindness due to measles infection in children

Abstract: Routine vitamin A supplementation for the prevention of blindness due to measles infection in children (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 5 publications
1
11
0
3
Order By: Relevance
“…Measles: Vitamin A has been recommended for use in children with measles in developing countries as it appears to reduce complications and mortality. 28 Dermatology: Topical Retinoic acid is indicated for use in many hyperkeratotic and hyperproliferativeskindisorders. 29 Acute promyelocytic leukemia: All-trans-retinoic acid (ATRA, or tretinoin), a synthetic oxidative metabolite of retinoic acid, in conjunction with other standard chemotherapy, has been used in acute promyelocytic leukemia.…”
Section: Other Therapeutic Usesmentioning
confidence: 99%
“…Measles: Vitamin A has been recommended for use in children with measles in developing countries as it appears to reduce complications and mortality. 28 Dermatology: Topical Retinoic acid is indicated for use in many hyperkeratotic and hyperproliferativeskindisorders. 29 Acute promyelocytic leukemia: All-trans-retinoic acid (ATRA, or tretinoin), a synthetic oxidative metabolite of retinoic acid, in conjunction with other standard chemotherapy, has been used in acute promyelocytic leukemia.…”
Section: Other Therapeutic Usesmentioning
confidence: 99%
“…However, suprainfection may lead to permanent scarring and blindness. A Cochrane review by Bello et al 11 showed that vitamin A deficiency predisposes to more severe ocular complications and is one of the most common causes of acquired blindness in children in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the Cochrane Editorial Unit and 5 CRGs were commissioned to complete or update 12 reviews relating to vitamin A in advance of the guidelines process relating to the vitamin based on questions in the PICO format identified by a panel of experts identified by the WHO micronutrients group (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Since the work on vitamin A was completed, the Cochrane Editorial Unit has also contributed to work on other guidelines programs, including those on iron.…”
Section: What Is the Cochrane Collaboration?mentioning
confidence: 99%